(untitled) (Equilibrium: Jurnal Pendidikan, 2021)
Abstract. English has an important role in the sustainable tourism sector through communication media with the aim of promoting abroad, service, good communication between foreign tourists and tourism actors, and the surrounding community which ultimately relates to the development of local tourism progress in the sustainable tourism sector in the industrial era. 4.0. Tourist actors must master English, especially the surrounding community, namely simple conversation, mastery of language and basic conversation. This study aims to examine the Benefits of English-Speaking Culture in the Sustainable Tourism Sector in the Industrial Era 4.0 in Gorontalo Province. The analytical method used is descriptive qualitative analysis. This paper shows that English-speaking culture in the sustainable tourism sector in the industrial era 4.0 in Gorotalo Province is needed with the aim of increasing foreign tourist visitors, facilitating communication using English and also as a promotional event abroad about local tourist destinations in the Province. Gorontalo. English has an important role in the tourism sector as a basis for people around tourist destinations and those who work in the tourism industry to be able to communicate well using English. Abstrak. Bahasa Inggris memiliki peran penting dalam sektor pariwisata berkelanjutan melalui media komunikasi dengan tujuan sebagai promosi ke luar negeri, pelayanan, komunikasi yang baik wisatawan asing dengan pelaku wisata, dan masyarakat sekitar yang pada akhirnya berhubungan dengan pengembangan kemajuan wisata lokal pada sektor pariwisata berkelanjutan di era industri 4.0. Pelaku wisata harus mengusai Bahasa Inggris terutama masyarakat sekitar yakni percakapan sederhana, penguasaan bahasa dan percakapan dasar. Penelitian ini bertujuan mengkaji Kemanfaatan Budaya Berbahasa Inggris Pada Sektor Pariwisata Berkelanjutan di Era Industri 4.0 di Provinsi Gorontalo. Metode analisis yang digunakan adalah analisis kualitatif deskriptif. Tulisan ini menunjukkan bahwa budaya berbahasa Inggris pada sektor pariwisata berkelanjutan di era industri 4.0 di Provinsi Gorotalo sangat diperlukan dengan tujuan untuk meningkatkan pengunjung wisatawan asing, memperlancar komunikasi dengan menggunakan Bahasa Inggris dan juga sebagai ajang promosi ke luar negeri tentang destinasi wisata lokal yang ada di Provinsi Gorontalo. Bahasa Inggris memiliki peranan penting dalam sektor pariwisata sebagai dasar bagi masyarakat sekitar destinasi wisata dan yang bekerja di industri pariwisata agar mampu berkomunikasi dengan baik menggunakan Bahasa Inggris.